A influência do estágio supervisionado na empregabilidade dos alunos do curso Engenharia de Produção da UERJ - Sereno, Hayane Alvarenga; Marconcini Bittar, Rita de Cássia da Silveira; de Almeida, Filipe Careli; de Barros, José Glenio Medeiros (Revista Gestão da Produção Operações e Sistemas, 2007)
The present work describes a research accomplished at the Technology College (FAT) of the Rio de Janeiro StateUniversity (UERJ), which aimed at investigating and analyzing the situation of the interns, who were studentsfrom the Production Engineering Course at FAT/UERJ, in the south region of the Rio de Janeiro state. By meansof information obtained by the research, a database was elaborated, and several analyses were developed fromthis database. The obtained results have demonstrated the situation of FAT/UERJ students regarding the supervisedinternship in the job market in the region, as well as the employability level of the interns, taking intoconsideration the largest enterprise surveyed in the region.Keywords: Supervised Internship; Production Engineering; UERJ.